(untitled) (Gestão & Regionalidade, 2015)
Emerging countries have adopted public policies of foreign trade that prioritize trade strategies of business internationalization such as Zonas de Processamento de Exportação (ZPE) [Export Processing Zones]. In Brazil, the company ZPE CEARÁ was established by the state of Ceará with a mission to deploy the ZPE do Pecém, the first of these areas to operate. This research aims to identify and characterize the facilitative conditions and limiting aspects of the implementation process of the company ZPE CEARÁ under the perspective of the Institution-Based View, concluding that factors related to this theory influenced the deployment process of the company, especially regarding facilitative conditions.